Аналіз нових підходів та практик у системі наукового рецензування - Ковалик, Лілія; Березко, Олександр (Видавництво Львівської політехніки, 2019)
Today Open Peer Review, an important part of Open Science, gains popularity among academic publishers all over the world. However, due to increasing amount of means and solutions, the concept becomes fuzzy and needs analyzis. We consider the most popular ones in order to shape the vision for implementing such a system in Ukraine.
Keywords: рецензування; відкрите рецензування; наукова стаття; видавничий процес; якість наукових рецензій